Alternative procedure for urinary bladder clot evacuation - a case report - Islam, M S; Rahman, S; Hossain, M; Islam, S; Islam, K M; Alam, A K M K (Bangladesh Journal of Urology, 2012)
Along with different methods for the treatment option of urinary bladder clot removal, mechanical procedure for clot dissolution and removal also becoming popular. In this report we present a case of large organized post prostatectomy urinary bladder clot in a 90 years old patient by using simple operating room suction apparatus connecting with a Nelatons catheter and its effectiveness. BJU 2010; 13(2): 78-79